Research on Dual-loop Controlled Grid-connected Inverters on the Basis of LCL Output Filters - Huang, Huichun; Hu, Renjie; Yi, Guiping (Elektronika ir Elektrotechnika, 2014)
Under the premise that the same high-frequency filtering effect is realized, comparing with an L filter, an LCL filter, requiring less total inductance is more suitable for the application in grid-connected devices with low switching frequency and high power, but easier to cause current or voltage resonance and spike, thus further affecting the stability of the system. The design of the parameters not only influences the elimination effect of the ripple at the switching frequency, but also has impact on the operation performance of the devices. This paper establishes the mathematical models of inverter and LCL filter, adopts direct current dual-loop control strategy and analyses the stability, provides design analysis to LCL filter and gives the constraint and restriction conditions for the design of parameters. Moreover, this paper also carries out simulated research by means of Simulink and conducts experiments on the basis of the sample machine established. The result proves the correctness of the control strategy and design analysis herein. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.5589